THE ANALYSIS OF BANK PERFORMANCE IN PT. BANK NEGARA INDONESIA, TBK AND PT. BANK RAKYAT INDONESIA,TBK BASED ON FINANCIAL RATIO - Kosasih, Dwi (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Bank is one financial institution that supports the growth and development of the economy of a country. Banks in Indonesia have several functions, one of it is to save money and make loans to the public. Bank also has a number of purposes such as to improve the quality of service and most importantly to give satisfaction to the consumer. The quality of a bank can be seen from the performance of the bank, if the bank is a good performance management system means the bank is also good. This study aimed to compare the performance of the bank BNI and BRI, the performance of the two banks is measured by financial ratios such as ROA, ROE, NIM, CAR, LDR, NPL during the period year of 2004-2012. This type of research is a comparative study with secondary data collection techniques. Independent sample t - test was used to test the average difference. The conclusion of this study is on the period 2004-2008 there is a performance difference between the BNI and BRI bank seen from the CAR. And in the period 2009-2012 there is a performance difference between the BNI and BRI bank seen from the CAR, NPL, and LDR.And in the period 2009-2012 there a performance difference between the BNI and BRI bank seen from the CAR, NPL, LDR. BNI and BRI needs to control their asset, loan and uphold the principles of prudential banking in lending to increase their profit. Keywords: bank Performance, ROA, ROE, NIM, CAR, NPL, LDR, BNI, BRI.